Social determinants of health and upper gastrointestinal cancer outcomes in the United States: a systematic review - Santellano, Brenda; Agrawal, Rashi; Duchesne, Gabriela; Sharara, Muhannad; Agrawal, Gagan; Balas, E. Andrew; Tsai, Meng-Han; Nayak, Asha; Cortes, Jorge E. (Frontiers in Public Health, 2024)
IntroductionSocial determinants of health (SDOH) are the conditions in which individuals are born, grow, work, live, and age.MethodsWe examined the literature on the association between SDOH and survival of patients with gastrointestinal (GI) cancer [esophageal, duodenal and gastric cancer (GC)] in the United States from 2001 to 2022.ResultsFrom 38,654 studies across COCHRANE, EMBASE, SCOPUS, WEB OF SCIENCE, and PubMed, we identified 14 relevant studies focusing on GI cancer using the PRISMA flowchart. Eight of the 12 GC studies specifically focused on gastric adenocarcinoma (GAC), the most common histologic subtype. Uninsured patients had a significantly worse overall survival probability. For patients with GI cancer, the highest income level (i.e., in the highest quartile) was associated with improved survival. Being unmarried had a negative impact on overall survival. Overall, people with insurance, higher incomes, and who were married had better overall survival rates.DiscussionOur findings suggest a clear association between SDOH and survival for patients with GI cancers. However, there is great variability in the factors studied and how these are measured and reported. A better understanding of SDOH is needed to design strategies with an aim to improve patient outcomes.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, PROSPERO (CRD42022346854).